Enhancing Students' Writing Abilities through the Utilization of Visme Infographics - Sari, Mufida Naima; Luqman Al Hakim; Atik Astrini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve students’ ability in writing procedure texts through the use of Visme-based infographic media. The research is conducted using a Classroom Action Research (CAR) design involving 32 students of class XI F-11. The use of Visme resulted in a significant improvement in students’ average writing score, with a gain score of 17.4 points. The results indicate that visual-supported writing through infographic media enhances structure, vocabulary use, and coherence.